2018
DOI: 10.3767/persoonia.2018.40.09
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of gall-forming rusts (Uromycladium, Pucciniales) on Acacia in Australia

Abstract: Uromycladium tepperianum has been reported on over 100 species of Acacia, as well as on the closely related plant genera, Falcataria, Racosperma and Paraserianthes. Previous studies have indicated that U. tepperianum may represent a complex of host-specific, cryptic species. The phylogenetic relationships between 79 specimens of Uromycladium were determined based on a concatenated dataset of the Small Subunit, the Internal Transcribed Spacer and the Large Subunit regions of nuclear ribosomal DNA, and the mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…According to Stukenbrock and McDonald (2008), the emergence of new pathogens occurs through mechanisms such as host jumps, co‐evolution, hybridization and horizontal gene transfer. Doungsa‐ard et al (2015, 2018) proposed that rust disease of F. moluccana involves a speciation mechanism involving a jump from acacia, in contrast to co‐evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Stukenbrock and McDonald (2008), the emergence of new pathogens occurs through mechanisms such as host jumps, co‐evolution, hybridization and horizontal gene transfer. Doungsa‐ard et al (2015, 2018) proposed that rust disease of F. moluccana involves a speciation mechanism involving a jump from acacia, in contrast to co‐evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Nielson in Australia (Burges, 1934; Morris, 1987; Old et al, 2000). Doungsa‐ard et al (2015, 2018) further proposed a new name for gall rust in F. moluccana as U. falcatariae . The data of morphological and phylogenetic analysis showed that the gall rust pathogen in F. moluccana was taxonomically different from U. tepperianum which infected acacias.…”
Section: Introductionmentioning
confidence: 99%
“…Whether U. acaciae is a complex of species remains a knowledge gap. However, intraspecific variability of rDNA is known in other species of Uromycladium (Doungsa‐ard et al, 2018) and other rust fungi (Rush et al, 2019). Resolution of this taxonomic uncertainty and the possible existence of a complex of species will hinge on wide sampling of this rust in its native range and application of molecular markers other than rDNA.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, staff at BRIP have taken a prominent role in using molecular methods to unravel cryptic diversity in plant pathogenic fungi. This work has led to revisions and taxonomic contributions to our knowledge of the diversity of Australian downy mildews [10][11][12] , smuts [13][14][15] , rusts [16][17][18][19] and some important plant Interest in bacteria and fungi as an untapped resource for novel bioactive natural products (enzymes, proteins, primary and secondary metabolites) has gained momentum in recent years. Over 50% of all pharmaceutical drugs currently on the market are directly derived from or inspired by natural products 28 .…”
Section: In Focusmentioning
confidence: 99%